An efficient Manta Ray Foraging Optimization algorithm for parameter extraction of three-diode photovoltaic model. (September 2021) - Houssein, Essam H.; Zaki, Gamela Nageh; Diab, Ahmed A. Zaki; Younis, Eman M.G.
Abstract: The Parameter estimation of solar cell models is considered an important problem in the computational simulation and design of photovoltaic (PV) systems. In this paper, the PV parameters of single, double, and triple-diode models are extracted and tested under different environmental conditions. The parameter estimation of the three models is presented as an optimization process with an objective function to reduce the difference between the measured and calculated data. Moreover, a new optimization algorithm for extracting the PV parameters of the single, double, and three-diode models called the Manta Ray Foraging Optimization (MRFO) algorithm has been proposed. The results show that the obtained parameters are the optimal values and give the least difference between the measured and calculated data compared with other algorithms. Graphical abstract: Highlights: Manta ray foraging optimization (MRFO)is used to determine the variables of the Photovoltaic (PV). MRFO can get the optimal values of the PV parameters of the single, the double and the three diode models. A comparison has been done between the MRFO with other metaheuristic algorithms. The results show that MRFO gave the least difference between the calculated values and the actual values.